Monitoring Morphological and Optical Properties on Hybrid Porous Polymer Films - Sanchez-Poblete, J (Taylor and Francis Inc., 2017)
This work focuses on an optical and morphological comparative study of hybrid functional polymer porous films on glass substrates using the spin coating technique. The covering of these membranes, by a predeposited Zn2+ seed layer, was done applying the dip casting technique, which allows the synthesis of a large area and the control of the orientation of ZnO nanoparticles. It was possible to observe changes on the optical properties and surface morphology, which were attributed to both the spatial structure of the macromolecule and their interaction with the inorganic nanoparticles. It was also clear that hybrid porous matrices exhibit a blueshift with decreasing particle size. © 2017 Taylor & Francis Group, LLC.